2003
DOI: 10.1172/jci16293
|View full text |Cite
|
Sign up to set email alerts
|

α1-adrenergic receptors activate Ca2+-permeable cationic channels in prostate cancer epithelial cells

Abstract: . Y. Shuba's present address is: Bogomoletz Institute of Physiology, Kiev, Ukraine. Conflict of interest:The authors have declared that no conflict of interest exists. Nonstandard abbreviations used: α1-adrenergic receptor (α1-AR); human prostate cancer epithelial cell (hPCE cell); phospholipase C (PLC); inositol triphosphate (IP3); diacylglycerol (DAG); transient receptor potential (TRP); α1A subtype of α1-AR (α1A-AR); lymph node carcinoma of the prostate cells (LNCaP cells); intracellular Ca 2+ concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…First, gadolinium influx was significantly reduced in specific TRPC knockdown monocytes compared with control monocytes. Second, several investigators reported that SKF-96365 is able to reduce cation influx through TRPCs [32,[34][35][36]. In accordance with these findings, in the presence of SKF-96365, gadolinium and sodium influx were significantly reduced in our study.…”
Section: Discussionsupporting
confidence: 92%
“…First, gadolinium influx was significantly reduced in specific TRPC knockdown monocytes compared with control monocytes. Second, several investigators reported that SKF-96365 is able to reduce cation influx through TRPCs [32,[34][35][36]. In accordance with these findings, in the presence of SKF-96365, gadolinium and sodium influx were significantly reduced in our study.…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence in the literature for 2-APB blockade of store-independent calcium entry, including that activated by acetylcholine in PC12 adrenal chromaffin cells (49), by carbachol in murine gastric smooth muscle (27), and by ␣ 1A adrenoceptor agonists in prostate cancer epithelial cells (45,50). 2-APB also inhibits receptor-activated, store-independent calcium entry mediated by TRPC3 overexpressed in HEK293 cells (28,52).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are inconsistencies between the sequencing data and functional studies on α 1A -adrenoceptors and muscarinic receptors. Two papers have suggested a role for the α 1A -adrenoceptor in proliferation of LNCaP cells 149 and chemoresistance of DU145 cells; 150 however receptor detection was based on α 1A -drenoceptors antibodies, which are notorious for lack of specificity 151 . The muscarinic receptor agonist carbachol likewise stimulates proliferation of LNCaP cells despite an apparent lack of mRNA for any of the relevant acetylcholine receptor subtypes 135 …”
Section: Prostate Cancermentioning
confidence: 99%